The effect of enzymatic hydrolysis of pretreated wastepaper for bioethanol production - Hossain N.; Hoong L.L.; Barua P.; Soudagar M.E.M.; Mahlia T.M.I. (Springer, 2023)
Enzymatic hydrolysis of waste biomass for bioethanol production is considered a decades old traditional, inexpensive, and energy-effective approach. In this study, waste office paper was pretreated with diluted sulfuric acid (H2SO4) and hydrolyzed with one of the most available and cost-effective enzymes, cellulase derived from Trichoderma reesei, under submerged static condition. Three different pretreatment approachescut into 2 cm2, blended with distilled water, and pretreated with diluted H2SO4have been implemented, and pretreatment with diluted H2SO4 was the most effective. Hydrolysis with different concentrations0.5 M, 1.0 M, 1.5 M, 2.0 M of H2SO4was performed. The maximum glucose content was obtained at 2.0 M H2SO4 at 90 min reaction time, and glucose yield was 0.11 g glucose/g wastepaper. The cut paper, wet-blended, and acid-treated wastepaper was hydrolyzed with cellulase enzyme for 2, 4, and 5 consecutive days with 5 mg, 10 mg, 15 mg, and 20 mg enzyme loadings. The maximum glucose content obtained was 9.75 g/l from acid-treated wastepaper, after 5 days of enzymatic hydrolysis with 20 mg enzyme loading and a glucose yield of a 0.5 g glucose/g wastepaper. The wastepaper hydrolysate was further fermented for 6, 8, and 10 hours continuously with Saccharomyces cerevisiae (yeast), and at 10 hours of fermentation, the maximum glucose consumption was 0.18 g by yeast. Further, HPLC analysis of the fermented medium presented a strong peak of bioethanol content at 16.12 min. The distillation of bioethanol by rotary evaporator presented 0.79 ml bioethanol/fermented solution, which indicated the conversion efficiency of 79%. 2021, The Korean Institute of Chemical Engineers.